Analysis of raked pile using spun pile - Muhammad Harzarul Afiq Bin Johar (School of Environmental Engineering, University Malaysia Perlis, 2014)
The main purpose of this analysis is to know how raked pile resist toward load compare using pile group only how it resist is depend on inclination of pile.The objectives of this project are to study and identify settlement value of pile cap at two different point with variable length of pile (18m , 25m , 30m) on two type of soil (clay and sand) , to identify maximum displacement for each pile (left and right) with variable length of pile (18m , 25m , 30m) on two type of soil (clay and sand) and to study and identify relation between pile diameter value toward settlement value at one point on different type of soil (clay and sand).